Características morfogênicas e estruturais de híbridos de sorgo submetidos a adubação nitrogenada - Silva, Wilton L. [UNESP]; Basso, Fernanda C. [UNESP]; Ruggieri, Ana C. [UNESP]; Vieira, Bruno R. [UNESP]; Alves, Pedro L. C. A. [UNESP]; Rodrigues, José A. S. (Revista Brasileira de Ciencias Agrarias, 2012)
The effect of two topdressing nitrogen doses was evaluated on the morphogenetic and structural characteristics of sorghum hybrids (Sorghum bicolor (L.) Moench) BRS 801 and 0734006, cultivated in vases in open-air conditions. A completely randomized design was used with four treatments arranged in factorial outline 2x2 (two sorghum hybrids and two nitrogen doses, 50 and 100 kg ha-1), with eight replications per treatment. There was a significant effect of interaction hybrid x fertilization on the leaf appearance rate, the hybrid BRS 801 being more responsive to the increased nitrogen dose. The phyllochron, the total number of leaves and leaf elongation rate, were influenced both by nitrogen doses and by hybrids. The leaf senescence rate was not influenced by factors fertilization and hybrids. These variations in morphogenetic and structural characteristics between the hybrids and/or nitrogen doses, probably indicate that hybrids respond in a different way to topdressing.
Morphogenetic and structural characteristics of sorghum hybrids submitted to the nitrogen fertilization
Keywords: Annual forage; Leaf appearance rate; Leaf elongation rate; Nitrogen; Phyllochron; Bovine respiratory syncytial virus; Sorghum bicolor